2010
DOI: 10.1007/s13233-010-0701-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of ethylcellulose-based microcapsules for sustaining release of a model fragrance

Abstract: A model fragrance, vanillin, was encapsulated into ethylcellulose using an oil-in-water solvent evaporation method to prepare biodegradable microcapsules that can sustain the release of the model agent and potentially be bound to textile material. This study examined the effect of vanillin and polymer concentrations on the encapsulation efficiency, vanillin content and size of microcapsules. Microcapsules were dip-coated by chitosan, and the coating was crosslinked with non-toxic 1,2,3,4-butanetetracarboxylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…It has been proved that the aroma perception is maintained for several days in fabrics if fabrics impregnated with capsules containing perfume and the capsules continue to emit aroma for up to five wash cycles. [11][12][13] Fragrance encapsulated in small particles (nanometer range) and narrow dispersion are preferred for use in textiles as they can provide a strong adhesive force and interact with the fibre due to their large surface area. [14] Furthermore, the smaller the capsules the greater the covering of the product and the longer the fragrance will last because it takes longer for the capsules to be ruptured by physical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that the aroma perception is maintained for several days in fabrics if fabrics impregnated with capsules containing perfume and the capsules continue to emit aroma for up to five wash cycles. [11][12][13] Fragrance encapsulated in small particles (nanometer range) and narrow dispersion are preferred for use in textiles as they can provide a strong adhesive force and interact with the fibre due to their large surface area. [14] Furthermore, the smaller the capsules the greater the covering of the product and the longer the fragrance will last because it takes longer for the capsules to be ruptured by physical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in our previous studies PVA was found to be a very effective surfactant for emulsifying EC containing organic droplets in the aqueous phase [12][13][14]. Nevertheless, we also examined the usability of other emulsifiers, such as Tween 80, polyvinylpirrolidone and poloxamer (Pluronic F68) beside PMAA.…”
Section: Resultsmentioning
confidence: 99%
“…The results were processed by using the thermoanalyzer's Calisto Processing (v1. 12) software. The corresponding melting/freezing enthalpies, and onset temperatures were determined by the baseline integration method (Tangential sigmoid baseline type).…”
Section: Analysis Of Microcapsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often used as food preservative (Rakchoy et al, 2009), constituent in cosmetics and drug preparations (Hossain, 2011), textile fragrance (Peña et al, 2012;Feczkó et al, 2010) and cross-linker (Peng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%